Would You Like to Buy Food via Ecommerce App? The Mediating Role of Brand Image in Electronic Word of Mouth, Perceived Ease of Use, and Purchase Intention - Jean Richard Jokhu; Avita Melinia Rahmawati (Faculty of Economics, Universitas Sriwijaya, 2022)
The rapid development of online food delivery applications in Indonesia currently makes Shopee launch a new feature, Shopee Food. By joining the online food delivery application market in Indonesia, Shopee Food must be able to compete with other online food delivery applications. This study aims to analyzed the factors that influencing purchase intention in Shopee Food. Using Brand Image as the mediating factor for Perceived Ease of Us and Electronic Word-of-mouth, this study tries to explain customer intention to purchase food in shopeefood. This study used quantitate method with purposive sampling to draw the espondent, with total 345 respondents. The findings of this study found that word-of-mouth, perceived ease of use plays significant role on user purchase intention in Shopeefood, and brand image also significantly mediate the relationship of perceived ease of use and word of mouth toward intention to use.